Reduction of PTEN and p27kip1 expression correlates with tumor grade in prostate cancer: analysis in radical prostatectomy specimens and needle biopsies - Dreher, Tina; Zentgraf, Hanswalter; Abel, Ulrich; Römer, Alexandra; Michel, Maurice Stephan; Bleyl, Uwe; Grobholz, Rainer (Virchows Archiv, 2004)
The extreme variability of prostate cancer implies latent disease with missing clinical symptoms in some cases. Tumor suppressors PTEN (phosphatase and tensin homolog deleted on chromosome ten) and p27kip1 are frequently mutated in various human cancers. PTEN negatively influences cell growth and induces apoptosis, while p27kip1 binds to cyclin-E-Cdk2 and counteracts mitosis. This study investigated the expression of PTEN and p27kip1 in prostatectomies and needle biopsies in order to determine whether protein localization or expression levels are correlated with tumor grade and whether PTEN and p27kip1 expression in biopsies are valuable predictive tumor markers. Analysis of PTEN demonstrated that weak expression levels were significantly more prevalent in high-grade tumors. Analysis of p27kip1 revealed that high-grade tumors had a higher percentage of cytoplasmic localization of the protein than low-grade tumors, where nuclear localization was more frequent. Furthermore, this study indicated a positive association between PTEN and p27kip1 levels. An increase of high-grade tumors corresponded to a progressive loss of both tumor suppressors in needle biopsies and prostatectomies. p27kip1 and PTEN did not show a higher predictive accuracy of the tumor grade in the surgical specimen than the Gleason score. However, p27kip1 had the same predictive value as the Gleason score in needle biopsies.